Analysis of nonspecific DNA synthesis during in situ PCR and solution-phase PCR. - Nuovo, G J; MacConnell, P; Gallery, F (Genome Research, 1994)
In this study we examine the factors that lead to nonspecific DNA synthesis during in situ PCR and solution-phase PCR. It was shown that primer-independent DNA synthesis can produce an intense signal during in situ PCR. This primer-independent pathway was apparently the result of the repair of DNA gaps induced by the heat treatment of the paraffin embedded tissue sections. This non-specific signal could be eliminated by blocking gap repair with dideoxy-TTP, avoiding heat treatment, or DNase pretreatment. The primer-independent signal was also influenced by the length and mode of fixation and the sample tissue itself. Elimination of the primer-independent signal and the use of viral primers in tissues that did not contain the virus showed that nonspecific DNA synthesis could be eliminated by the hot start modification. Primer oligomerization did not produce a signal during in situ PCR, even when it occurred robustly in the amplifying solution. Generation of the primer-independent signal in solution-phase PCR with purified DNA required a cross-linking fixative, heating, the addition of bovine serum albumin, and intact protein-DNA cross-links.